The frequency of, and attitudes towards, genetic testing amongst athletes and support staff. Issue 4 (February 2021) - Pickering, C.; Kiely, J.
Abstract: Recently, knowledge of the genetic influence on the attainment of elite athlete status, along with aspects such as training adaptations and injury risk, has grown. At present, there are various direct-to-consumer genetic tests targeted at athletes. Here, we aimed to determine to prevalence of, and attitudes towards, genetic testing in a group of athletes, coaches, and support staff. 243 participants (110 athletes and 133 support staff) took part in an internet-based survey. 51 % of athletes had competed internationally, and 54 % of support staff reported that their main contact time was with international athletes. The frequency of genetic testing was relatively low, with 10 % of athletes and 11 % of support staff stating they had utilised such a test. Overall, the majority of athletes and support staff felt that genetics played a role in the attainment of sporting success and training adaptation. The main barriers to undertaking genetic testing were a lack of awareness, high cost, and a lack of scientific evidence. The majority (73 % of athletes and 64 % of support staff) of participants utilising genetic tests found the information useful.